Development of a manual of specifications for dehydrated candied mango (Mangifera indica Linn) - Paguio Teresita C.; De Leon, Sonia Y. (1986.)
three drying pre-treatments in the production of dehydrated candied mango were employed: (1) sulfiting in 0.1% sodium metabisulfite solution, (2) 40-50-60°Bx step-up syruping and (3) addition of 0.25% citric acid and 0.10% sodium benzoate. Sensory evaluation results showed color and flavor to be the critical quality attributes. the established product profile described dehydrated candied mango as yellow orange, moderately plump, firm and tender and characteristic mango flavor. Objective and ubjective tests on rare-ripe mangoes, in-process slices and dehydrated candid mango were conducted to establish levels and tolerance for product evaluation. based on these, a manual of specifications for dehydrated candied mango was developed.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango, Candied -- Handbooks, manuals, etc